PENGARUH WORK FAMILY CONFLICT (WFC), STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PEREMPUAN HINDU DI UNIVERSITAS TABANAN - Ni Putu Sudarsani; Relin D.E; I Nyoman Temon Astawa (Pascasarjana Universitas Hindu Indonesia, 2026)
This study aims to analyze the influence of work-family conflict, job stress, and job satisfaction on the performance of Hindu female employees at Tabanan University. The study used a quantitative approach with a causal associative design. The sample population and the study consisted of 52 Hindu female employees, with data collection techniques using a Likert scale questionnaire. Data analysis was conducted through descriptive tests, classical hypothesis testing, and multiple linear regression analysis to examine the partial and simultaneous effects between variables. The results of the hypothesis testing indicate that partially, work-family conflict and job stress have a negative and significant effect on the performance of Hindu female employees, while job satisfaction has a positive and significant effect on performance. Simultaneously, work-family conflict, job stress, and job satisfaction have a significant effect on the performance of Hindu female employees at Tabanan University. These findings confirm that managing work-family conflict and job stress and increasing job satisfaction are important factors in improving the performance of female employees.